Growth of infant faecal bifidobacteria and clostridia on prebiotic oligosaccharides in in vitro conditions - Rada, Vojtěch; Nevoral, Jiří; Trojanová, Iva; Vlková, Eva; Šmehilová, Martina; Killer, Jiří (Anaerobe, 2008)
Our aim was to isolate bifidobacteria and clostridia from infant faeces and to test the growth of bifidobacteria and clostridia on prebiotic oligosaccharides. Seventy breast-fed infants aged between 3 and 253 days were tested for the presence of bifidobacteria and clostridia in their faeces. Ten strains of clostridia and 10 strains of bifidobacteria were isolated from infant faecal samples. Four strains of bifidobacteria originated from culture collections and 1 strain from fermented milk product were also tested. Subsequently, bacterial isolates were tested for their growth on prebiotic oligosaccharides in, in vitro conditions. Forty-six infants exhibited high numbers of bifidobacteria (usually higher than 9 logCFU/g) in their faeces. There were undetectable amounts of bifidobacteria in faecal samples in 24 of the studied infants (34%), these babies on the other hand possessed significant amounts of clostridia in their faecal flora. Both bifidobacteria and clostridia utilized all substrates tested. Bifidobacteria grew significantly better in the medium with galactooligosaccharides. Higher growth of clostridia was observed on raffinose and lactulose. Conversely, bifidobacteria grew slightly better in the medium with stachyose, inulin, Raftilose P85 and P95. However, these differences were not significant. Our results suggest that commercially available prebiotics support the growth of infant faecal clostridia. It is therefore questionable if bifidobacteria-deficient infants should be supplemented with prebiotics.
Keywords: Feces; Male; Colony Count, Microbial; Infant; Oligosaccharides; počet mikrobiálních kolonií; Clostridium; mužské pohlaví; novorozenec; lidé; oligosacharidy; ženské pohlaví; Humans; Infant, Newborn; Bifidobacterium; kojenec; Financing, Organized; kysané mléčné výrobky; Cultured Milk Products; Female; financování organizované; feces